Purification Of Epidermal Growth Factor By Displacement Chromatography - RAMESH BHAGAM; K.NAGAIAH; M. LAXMI NARASU; A.NARESH (International Journal of Pharma and Bio Sciences, 2012)
A method was developed based on displacement chromatography technique using inertsil ODS-3V, 4.6 x 250 mm, 5µ HPLC column for the purification of recombinant human Epidermal Growth factor. Care was taken starting from selection of suitable displace, displacer concentration, flow rate etc.We found that Methyltrialkyl (C8-C10) ammonium chloride (Adogen-464) was found to be suitable for separation of epidermal growth factor in purification process. This method was effective in achieving a purity of greater than 99 % with the recovery of 60% which had not been obtained in other chromatographic techniques and this method was proven to be ideal and cost effective.